Algeria : Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses key findings of the Financial System Stability Assessment on Algeria. The global crisis has had virtually no impact on Algeria's financial system, which remains stable overall but thoroughly underdeveloped. Pervasive exchange controls, widespread public ownership, and an abundance of domestic funding have protected banks from external shocks. Financial sector reforms have been pushed to the backburner by the emergence of global financial and regional political turmoil, with privatization of banks halted and consumer lending suspended. The authorities have also made progress in a number of areas implementing the recommendations of the 2007 Financial Sector Assessment Program update.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet